Effects of centrifuge loading on rock slope stability using numerical modelling - Rostami, Vahid (2022)
The shear strength of the rupture surface is often assumed to be the cause of a rock slope's stability. Natural slopes often feature discontinuous rupture surfaces composed of fractures and joints separated by massive rock blocks. In such cases, the strength of the rupture surface is composed of three components: friction, cohesion, and tensile strength. The structure of the rock slope, on the other hand, has a significant influence on rock slope stability. While the influence of the shear strength components, cohesion, and friction on slope stability is well established, little study has been conducted on the role of joint spacing in rock slope stability, which affects the shear and tension strengths of the rock layers in the rock slope. This study aims to determine the effect of joint spacing on rock slope when it fails in a toppling mode. The rock slope was constructed with a joint spacing of 10 mm based on a laboratory case study. In that case study, the joint set dips deeply into the slope surface, which results in a flexural toppling failure. In this research, rock slope with toppling failure is described as three various sizes of thin slabs of rock moving out of the slope and finally creating a rupture surface. These three joint spacings are smaller, actual, and bigger than the one joint spacing in the case study. Slip between the thin rock layers and tensile rupture across the slabs are both involved in the toppling process. Since there is only one joint set in that case study, only flexural toppling is addressed; as a result, another joint set is added to the rock slope as a secondary joint set to make the model more realistic. On the other hand, the secondary joint set dips in the opposite direction of the main joint set in order to investigate another kind of toppling. A mixture of cement, sand, and water was employed to create synthetic rock slope specimens. Taguchi and Response Surface Methodology (RSM) combined approaches were used to build the appropriate rock sample to run the other tests (such as the direct shear test) and verify the components to get the best results while decreasing the number of tests and the expense. The resultant combination was then used to create rock layers of varying thicknesses for geotechnical centrifuge testing and numerical modeling based on a distinct element framework. This study demonstrates that combining Taguchi and RSM techniques is an appropriate strategy for optimization. The experimental findings are within -0.69-0.90 percent of the model's expected values. In the numerical modeling approach, the impact of joint spacing is larger in the middle than in the crest. In the first model representing flexural toppling, failure occurred between 37 and 48 g, with a maximum displacement of two millimeters at the crest and 1.2 millimeters in the middle of the slope. While model B with block toppling failed in the range of 11 to 17 g and with displacements of 0.04 to 0.07 mm at the crest and 0.04 to 0.05 mm in the middle, its gravity loading was much lower. This study shows that the discontinuities inside the slabs of rock slopes are critical in developing the rupture surface. The spacing of rock slabs has a minor influence on toppling slopes, while adding a secondary joint set has a significant role in controlling the slope's stability. In addition, the created rupture surface influences the deformations in the crest and middle of the slope surface. The observed deformation patterns, the propagation of the rupture surface, and the initial condition of collapse were all in good agreement when the results of distinctive element modeling were compared to the results of laboratory scales. The findings suggest that the structure inside the rock slope significantly impacts the stability of toppling slopes.